Effect of stearic or oleic acid on milk performance and energy partitioning when fed in diets with low and high rumen-active unsaturated fatty acids in early lactation. (27th September 2019) - Yanting, Chen; Ma, Guiling; Harrison, Joseph H; Block, Elliot
Abstract: This experiment was conducted to determine the effects of stearic acid (SA ; C18:0) or rumen-protected oleic acid (OA ; C18:1 cis-9 ) on milk performance and energy partitioning of early lactation cows when supplemented in diets with low and high level of rumen unsaturated fatty acids (RUFA ). In low RUFA experiment (LRUFA ), FA supplement rich in either SA or calcium salts OA was added to a basal diet with a low concentration of RUFA (0.75% vs. 1.4%, LRUFA-SA vs. LRUFA-OA). In high RUFA experiment (HRUFA ), 2% soybean oil was added to the diet fed in the LRUFA experiment. In each experiment, 30 multiparous cows were blocked by parity and predicted transmitting ability for milk yield and were randomly fed 1 of 2 treatment diets from 2 to 13 wk postpartum. In the LRUFA experiment, LRUFA-SA had 2.4 kg/d more dry matter intake (DMI ) ( P < 0.01), 3.8 kg/d more energy-corrected milk ( P < 0.01), and 0.3% units more milk fat percentage ( P < 0.01) and 0.2 kg/d more milk fat yield ( P < 0.01). Dietary treatments did not affect body weight, energy balance, and energy intake partitioning into milk, maintenance, and body tissues ( P > 0.1). In the HRUFA experiment, HRUFA-SA had 1.4 kg/d more DMI ( P = 0.03) but similar milk and milk components yields ( P > 0.1). HRUFA-SA had a tendency to gain more body weight ( P = 0.07) and had more positive energy balance ( P = 0.01) and decreased gross feed efficiency (milk yield/DMI) ( P = 0.01). Consistently, HRUFA-SA increased intake energy partitioning into body tissues ( P = 0.02) and decreased energy partitioning into milk ( P = 0.01). In summary, SA supplementation had more DMI relative to OA, but the effects on milk and milk fat production were different and affected by the level of RUFA in the basal diet. In application, SA supplementation was more effective to improve milk production when included in the basal diet with the low RUFA.